Erlotinib therapy for Olmsted syndrome with p.L655P missense mutation in the TRPV3 gene: a case report - Zhang, Jia; Guo, MengYue; Yuan, DongYang; Wei, JinYang; Cui, Hongzhou (Frontiers in Medicine, 2025)
Olmsted syndrome (OS) is a rare disorder characterized by a mutilating palmoplantar keratoderma and periorificial keratotic plaques, but which shows considerable clinical heterogeneity. Recently, transient receptor potential vanilloid 3 (TRPV3) mutations associated with autosomal dominant or recessive OS have been reported. Here we describe a classically OS case with definitive diagnosis of OS based on clinical features and a genetic assay. Genetic analysis revealed heterozygous variants in the TRPV3 gene using whole-exome sequencing of case-parents’ trios. This mutation was not identified in his mother. Notably, a previously unreported heterozygous frameshift mutation, c.1964 T > C (p.L655P), was identified in exon 15 of the TRPV3 gene in this patient and his father. Additionally, the patient was effectively managed with oral erlotinib at a daily dose of 75 mg. After 3 months of treatment, most plantar lesions resolved, and the pain experienced was mildly alleviated. No significant adverse effects were observed in this case during treatment. In addition, we review the OS literature regarding TRPV3 gene mutations.